Baghdad at sunrise a Brigade Commander's war in Iraq - Mansoor, Peter R., 1960- (Yale library of military history., 2008)
An on-the-ground commander describes his brigade's first year in Iraq after the U.S. forces seized Baghdad in the spring of 2003, and explains what went right and wrong as the U.S. military confronted an insurgency, in a firsthand analysis of success and failure in Iraq.